2008
DOI: 10.1080/13561820701795069
|View full text |Cite
|
Sign up to set email alerts
|

Competence, respect and trust: Key features of successful interprofessional nurse-doctor relationships

Abstract: Professional relationships between doctors and nurses have often been seen as problematic, a barrier to effective collaborative practice, yet little is known about the intrinsic nature of such relationships in the primary care context. This study set out to explore roles of, and relationships between, nurses and doctors currently working in New Zealand primary care settings. Using a qualitative methodology, data were collected using in-depth interviews with 18 individual nurses and doctors working in primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 40 publications
3
147
1
2
Order By: Relevance
“…According to Pullon’s [21] research findings, working together for the common goal of patient health and recognising their respective skill sets leads to respect and interprofessional trust. Change in clinical practice behaviours as a result of IPE occurs when: (1) the education emphasises the participants’ common goals or experience; (2) encourages respect and trust; and (3) provides an opportunity to share differing opinions and experiences in a safe environment.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pullon’s [21] research findings, working together for the common goal of patient health and recognising their respective skill sets leads to respect and interprofessional trust. Change in clinical practice behaviours as a result of IPE occurs when: (1) the education emphasises the participants’ common goals or experience; (2) encourages respect and trust; and (3) provides an opportunity to share differing opinions and experiences in a safe environment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the positive change in the prestige sub-scale suggests the IPL activity assisted individuals to feel more respected by other professions. This has important implications for working interprofessionally in the future as highlighted by Pullon (2008). In her study exploring relationships between primary care nurses and doctors, Pullon identified that an understanding of one's own and the other health professionals' professional identities "… enabled demonstration of competence, the gaining of mutual respect and the ultimate development of resilient interprofessional trust" (2008: 142).…”
Section: Discussionmentioning
confidence: 99%
“…IPE strives to diminish the development of early stereotypes and positively influence the development of more positive professional attitudes. IPE is perceived as important for the development of mutual professional respect and trust (Pullon, 2008). Becoming a member of an interprofessional team is an experiential process requiring an interactive approach to learning.…”
Section: Introductionmentioning
confidence: 99%